1999
DOI: 10.1074/jbc.274.48.34483
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of Gαq/11 by an RGS Domain in the G Protein-coupled Receptor Kinase, GRK2

Abstract: ؊ . This revealed the specific ability of bovine brain G␣ q/11 to bind to both GRK2 and GRK3 in an AlF 4 ؊ -dependent manner. In contrast, G␣ s , G␣ i , and G␣ 12/13 did not bind to GRK2 or GRK3 despite their presence in the extract. Additional studies revealed that bovine brain G␣ q/11 could also bind to an N-terminal construct of GRK2, while no binding of G␣ q/11 , G␣ s , G␣ i , or G␣ 12/13 to comparable constructs of GRK5 or GRK6 was observed. Experiments using purified G␣ q revealed significant binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
300
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(324 citation statements)
references
References 50 publications
13
300
4
Order By: Relevance
“…In situations in which RGS proteins bind to GaGTP subunits but display little or no GAP activity on them, effector antagonism will occur. Sequestering of activated Gaq subunits has been observed for the RGS domain of the kinase of GPCRs type 2 (GRK2), thereby interfering in the regulation of phospholipase Cb (Carman et al, 1999). Similarly, sequestering of Ga subunits by RGS-R7 proteins reduces the effects mediated by m receptors in the CNS Sánchez-Blázquez et al, 2003, while that of Gaq by RGS-Rz proteins reduces calcium mobilization (Mao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In situations in which RGS proteins bind to GaGTP subunits but display little or no GAP activity on them, effector antagonism will occur. Sequestering of activated Gaq subunits has been observed for the RGS domain of the kinase of GPCRs type 2 (GRK2), thereby interfering in the regulation of phospholipase Cb (Carman et al, 1999). Similarly, sequestering of Ga subunits by RGS-R7 proteins reduces the effects mediated by m receptors in the CNS Sánchez-Blázquez et al, 2003, while that of Gaq by RGS-Rz proteins reduces calcium mobilization (Mao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All non-visual GRKs have a regulator of G-protein signalling (RGS) domain within the N-terminus region (Figure 1), which provides a potential mechanism by which GRKs might regulate GPCR signalling via phosphorylation-independent mechanisms. Indeed, growing evidence suggests that this could be the case for GRK2 and GRK3 [22][23][24] (Box 1). GRK4 -6 possess a highly conserved binding site (amino acids 22 -29 for GRK5) for phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2 ], which is thought to enhance catalytic activity [10].…”
Section: Grk Structure and Distributionmentioning
confidence: 99%
“…In a key study, Carman et al [22] revealed that although the N-terminal regulator of G-protein signalling (RGS)-like domains of GRK2 and GRK3 (see Figures 1 and 2 in the main text) possess only modest GTPaseactivating protein (GAP) activity, they bind avidly to activated Ga q/11 to inhibit inositol (1,4,5)-trisphosphate [Ins(1,4,5)P 3 ] generation. Crucially, the expression of this RGS-like domain alone can inhibit the ability of several GPCRs to stimulate PLC activity, while exerting no effect on cAMP production [23].…”
Section: Grk Structure and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven G protein receptor kinase (GRK) family members contain an N-terminal atypical RGS domain (Siderovski et al, 1996;Penn et al, 2000). Although very little is known about the function of the RGS domain in most of these proteins, it has been shown that the RGS domain of GRK2 binds to G␣ q/11 and inhibits G␣ q -mediated activation of phospholipase C-␤ (Carman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%